Studies on antidiabetic and other biological activities of Centratherum Anthelminticum / Aditya Arya - Arya, Aditya (2012)
In search of phytomedicine for diabetes, this preliminary screening was conducted on twelve (12) different plants for hypoglycemic activity and antioxidant potential in the in vitro and in vivo study models. Amongst all, Centratherum anthelminticum seeds demonstrated maximum hypoglycemic and antioxidant potential. Therefore, the defatted crude methanolic fraction of the Centratherum anthelminticum seeds (CAMFs) was selected for detailed antidiabetic activity on the in vitro cell-based biological studies on mouse pancreatic cells, β-TC6 and on type 1 and type 2 diabetic rats for 4-weeks. The results of this study indicate that CAMFs showed potential antidiabetic effect on β-TC6 cells and confirmed beneficial effects on type 2 diabetic rats by ameliorating hyperglycemia and augmenting insulin secretion without any toxic signs and lethality in acute toxicity studies. Furthermore, CAMFs was studied for H2O2-induced nuclear factor-κB (NF-κB) translocation effects on β-TC6 cells to investigate ROS-associated oxidative stress. Subsequently, a 12-week study was conducted on type 2 diabetic rats to determine biochemical parameters and their associated complications. The results of this study showed that CAMFs prevented H2O2-induced NF-κB translocation in the β-TC6 cells and downregulated hyperglycemia, oxidative stress, dyslipidemia and inflammatory response in diabetic rats. Next, the crude fractions of Centratherum anthelminticum seeds were evaluated for pleotropic biological activities which had not been investigated on this plant. The result of this study showed that, defatted crude chloroform fraction (CACF) posesses the highest level of pleotropic bioactivities. CACF was tested on RAW264.7 macrophages for tumor necrosis factor-α (TNF-α) inhibition and for cytotoxic effects on targeted A549, PC-3, MCF-7, and WRL-68 cancer cell lines, along with antioxidant potential on DPPH, FRAP and ORAC assays. Results of this study demonstrated that CACF exhibited the strongest inhibitory effects on TNF-α secretion and possessed maximum cytotoxic effects on MCF-7 cancer cells, with antioxidant abilities. Furthermore, we observed dose-dependent inhibitory response of CACF on serum TNF-α inhibition on lipopolysaccharides (LPS)-stimulated SD rats. Moreover, in line with the cytotoxic effects, CACF showed inhibitory role against the activation of NF-κB translocation in MCF-7 cells, dose-dependently. It was concluded that CAMFs may be of interest in the pharmaceutical industry to be developed as a dietary supplement for the management of type 2 diabetes and its associated complications. Moreover, CACF fraction could be suggested for the alleviation of elevated inflammatory response as well as in the management of breast cancer and oxidative stress.